In search of textual boundaries: A case study on the transmission of scientific writing in 16th-century England. Lectio praecursoria - Varila Mari-Liisa (Finland, 2022)
The author defended her doctoral dissertation In Search of Textual Boundaries: A Case Study on the Transmission of Scientific Writing in 16th-Century England (Anglicana Turkuensia 31, Turku 2016) at the Faculty of Humanities, University of Turku, on 28 May, 2016. The opponent at the public defence was Professor Daniel Wakelin (University of Oxford), and the defence was chaired by Professor Matti Peikola (University of Turku). The following is an English translation of the introductory talk delivered in Finnish at the start of the viva.